Mathematical Model of Separation of Transplutonium andRare Earth Elements by Ion-Exchange Chromatography Method with Complexation During Elution; Chemical Engineering Transactions; Vol. 52 - Chursin Yu. A. Yuri Alexandrovich; Gozhimov A. I. Aleksandr Igorevich; Liventsov S. N. Sergey Nikolaevich; Shmidt O. V. Olga Vitaljevna (2016, 2016)
Title screen